ADVANTAGE: Advanced discovery of visceral analgesics by neuroimmune targets and the genetics of extreme human phenotype, a study protocol - Marco Vinicio Alban-Paccha; Nicholas Shenker; Jimena Teran-Perez; Andrew W. Horne; George G. Malliaras; Christopher Geoffrey Woods (PLoS ONE, 2026)
Chronic visceral pain affects over 20% of adults globally but remains poorly understood, significantly impacting quality of life and healthcare costs. Limited understanding and diagnostic misconceptions hinder effective management, particularly during acute pain flares. This study aims to clarify underlying mechanisms and improve clinical management by combining detailed phenotyping, genetic analysis, immunological profiling, pain mapping, and wearable sensor data in three cohorts: Extreme Visceral Pain, Lack of Visceral Pain, and Healthy Controls. Participants with diverse visceral conditions, such as polycystic kidney disease, inflammatory bowel disease, chronic pancreatitis, endometriosis, painful bladder syndrome, vaginal mesh complications, and fibromyalgia, are recruited via clinical referrals from NHS Cambridge University Hospitals and NHS Lothian. Healthy control volunteers are recruited locally. Data collection involves daily pain ratings captured through a mobile app, wearable physiological monitoring, quantitative sensory testing, detailed medical and lifestyle questionnaires, and bio-sample analyses (genetic variants, autoantibodies). The primary confirmatory outcome evaluates the correlation between wearable sensor parameters and self-reported visceral pain intensity. Genetic analyses, including functional SNP allele discovery and Mendelian gene effect analysis, and immunological profiling will explore underlying biological mechanisms. Challenges anticipated include potential compliance and technical difficulties in remote data collection, potentially affecting data quality. Findings will be disseminated widely, aiming to refine diagnostic tools and inform treatment strategies, ultimately enhancing patient care and outcomes in chronic visceral pain management.